2021
DOI: 10.1007/s11469-021-00714-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Responding to Substance Use and Abuse in the Palestinian Refugee Camps in Lebanon Prior to and During COVID-19 Times

Abstract: Due to its geographical proximity to the Syrian conflict and the occupied territories, Lebanon has experienced an influx of refugees in recent times. Palestinian refugees are an identified key vulnerable population, with displaced communities increasingly experiencing camp insecurity, vulnerability to drug use and related health harms. A qualitative study consisting of in-depth interviews and focus group discussions (FGDs) was undertaken as part of a regional exercise investigating Palestinian community experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A previous study in Uganda with refugees showed high prevalence of post-traumatic stress, major depressive, generalized anxiety and substance use disorders, all linked to unmet basic needs (Bapolisi et al, 2020). Conversely, interventions addressing social determinants, for example, income-generating programs, can act as protective factors against initial AUD development (Amosu et al, 2016;Aaraj et al, 2021;Naseh et al, 2021), while potentially preventing relapse posttreatment. Failing to recognize the impact of social determinants on mental health and AUDs will impede efforts in prevention, recovery and symptom reduction, especially in resource-poor settings.…”
Section: Policy Impact Pathwaymentioning
confidence: 99%
“…A previous study in Uganda with refugees showed high prevalence of post-traumatic stress, major depressive, generalized anxiety and substance use disorders, all linked to unmet basic needs (Bapolisi et al, 2020). Conversely, interventions addressing social determinants, for example, income-generating programs, can act as protective factors against initial AUD development (Amosu et al, 2016;Aaraj et al, 2021;Naseh et al, 2021), while potentially preventing relapse posttreatment. Failing to recognize the impact of social determinants on mental health and AUDs will impede efforts in prevention, recovery and symptom reduction, especially in resource-poor settings.…”
Section: Policy Impact Pathwaymentioning
confidence: 99%
“…There is a scarcity of data about the health response and situation of people who use drugs (PWUD) during the pandemic in the Middle East and North Africa (MENA) region (Aaraj et al, 2021;Van Hout et al, 2022). A mixed method study was conducted by the MENA Harm Reduction Association (MENAHRA) to assess the situation of PWUD and impacts on harm reduction services in these countries, including Jordan, during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Replication studies are needed to adapt these interventions in diverse populations and to evaluate the consistency and sustainability of intervention effects. The unique context of forced displacement also necessitates a trauma‐informed approach and consideration of the social and structural determinants, including stigma and gender considerations, which influence SUD and engagement in care [17, 18]. Examples include integrating substance use services into existing and accessible systems of care to reduce stigma and tailoring outreach strategies by gender to promote acceptability and engagement.…”
mentioning
confidence: 99%